Virtual labs and their impact on developing scientific inquiry skills in the science subject for fifth-grade female students in Jeddah - Gahm, Fatima Ebrahim (Journal of Educational and Psychological Sciences, 2021)
The aim of the current research is to reveal the impact of virtual labs on developing scientific investigation skills of fifth-grade primary students in Jeddah, and in order to achieve that, the researcher used the quasi-experiment approach with one group, where the research tools were applied after ensuring their validity and stability, namely the performance test and the attached observation card, before After applying the experimental treatment material represented in the virtual Crocodile laboratory in a sample of (35) female students of the fifth grade of primary school - the second semester of the academic year 1437-1438 AH, and they were chosen by the intentional method, and after conducting the experiment the research results were analyzed, and the research concluded A total of a set of results, the most prominent of which is the existence of a statistically significant difference at the level of (0.05) between the mean scores of the experimental group students that use (virtual laboratories), in the pre and post application of the performance test and its observation card for scientific inquiry skills in favor of the post application. The researcher recommended employing virtual laboratories in teaching science subjects and its branches and suggested a set of future researches in light of the results of the research.
Keywords: Virtual Labs; scientific inquiry skills